2014
DOI: 10.3109/01902148.2014.971921
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of threeflexiVentsystem configurations using mechanical test loads

Abstract: The sole commercial system currently employing the forced oscillation technique (FOT) in small laboratory animals (flexiVent; SCIREQ Inc., Canada) was recently redesigned along with its operating software. Yet, many users still work with the legacy version or a mixed configuration. This study aimed to compare result accuracy and precision between three flexiVent system configurations and to quantify the impact of configuration changes on measured parameters. Physiologically relevant resistance or elastance wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
(27 reference statements)
1
10
0
Order By: Relevance
“…Our data indicate differences in measurements between the FV-M2 and FX3 flexivent systems, a difference that has also been observed by other groups [ 48 ]. One study found that there was no difference in precision or accuracy in resistance between the models; however, the FX system resulted in more accurate compliance measurements [ 48 ]. Therefore, the difference in significance in the parameters measured in 4DPI RSV infected female cotton rats between the different instruments may have been partly attributed due to their varying configuration.…”
Section: Discussionsupporting
confidence: 86%
“…Our data indicate differences in measurements between the FV-M2 and FX3 flexivent systems, a difference that has also been observed by other groups [ 48 ]. One study found that there was no difference in precision or accuracy in resistance between the models; however, the FX system resulted in more accurate compliance measurements [ 48 ]. Therefore, the difference in significance in the parameters measured in 4DPI RSV infected female cotton rats between the different instruments may have been partly attributed due to their varying configuration.…”
Section: Discussionsupporting
confidence: 86%
“…3t), which together indicated reduced lung compliance and distensibility. Further analysis using broadband forced oscillation maneuvers 16 revealed that SARS-CoV-2-infected mice at 7 dpi had relatively normal Newtonian resistance ( Fig. 3u), which is primarily a reflection of resistance in larger conducting airways.…”
Section: Pathophysiology Of Sars-cov-2 Infectionmentioning
confidence: 97%
“…Oxygen saturations were measured using the MouseOx Plus pulse oximeter (Starr Life Sciences, Oakmont, PA, USA) via the thigh sensor. Lung mechanic parameters were generated from the flexiVent rodent ventilator using the forced oscillation technique as previously described [ 10 ].…”
Section: Methodsmentioning
confidence: 99%